2007
DOI: 10.1089/acm.2006.6297
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Mixtures Containing the Mushroom Ganoderma lucidum Improve Recovery Time in Patients with Herpes Genitalis and Labialis

Abstract: Administration of WTTCGE to patients suffering from herpes genitalis and labialis appears to shorten the time required to obtain symptom relief as has been shown in a previous report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 4 publications
0
18
0
1
Order By: Relevance
“…The samples were analysed using either mass spectrometry, gas chromatography, isotope ratio mass spectrometry or infrared laser spectrometry, based on the micro-organisms under investigation and the sensitivity of the instrumentation required. Five studies (Agrawal et al, 1997;Cai et al, 2009;Hijikata et al, 2007;Gotteland et al, 2008;Wright et al, 2009) reported statistical significance in benefit claims of the PFS on specific outcomes against the different infectious diseases. Urine dip stick test Bailey, 2007, Mcmurdo 2005 Helicobacter pylori bacteria Quick and inexpensive method Non-quantitative 13 C urea breath test Shmuely, 2007, Gotteland, 2008, Nakajima, 2006 Helicobacter pylori bacteria Non-invasive, quick method Non-quantitative…”
Section: Methods For Evaluating the Benefits Of Pfs As Anti-infectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…The samples were analysed using either mass spectrometry, gas chromatography, isotope ratio mass spectrometry or infrared laser spectrometry, based on the micro-organisms under investigation and the sensitivity of the instrumentation required. Five studies (Agrawal et al, 1997;Cai et al, 2009;Hijikata et al, 2007;Gotteland et al, 2008;Wright et al, 2009) reported statistical significance in benefit claims of the PFS on specific outcomes against the different infectious diseases. Urine dip stick test Bailey, 2007, Mcmurdo 2005 Helicobacter pylori bacteria Quick and inexpensive method Non-quantitative 13 C urea breath test Shmuely, 2007, Gotteland, 2008, Nakajima, 2006 Helicobacter pylori bacteria Non-invasive, quick method Non-quantitative…”
Section: Methods For Evaluating the Benefits Of Pfs As Anti-infectivesmentioning
confidence: 99%
“…Cranberry has been the most studied plant used in PFS for its anti-bacterial properties in treating urinary tract infections and shows activity against Helicobacter pylori, the bacteria that causes stomach ulcers. 10 Prunus armeniaca L. (Armeniaca vulgaris Lam., Apricot) Nakajima, 2006 Different study designs were used ranging from an open trial with no placebo or control and no randomization (Bailey, Dalton, Daugherty, & Tempesta, 2007;Hijikata, Yamada, & Yasuhara, 2007;Maek-a-nantawat, Phonrat, Dhitavat, Naksrisook, Muanaum, Ngamdee, & Pitisuttithum, 2009;Nakajima, Fujita, Inoue, Nishio, & Seto, 2006;Davis, Shen, & Cai, 1990;Caporaso, Smith, & Eng, 1983) to double blind randomized placebo controlled trial including crossover (Mcmurdo, Bissett, Price, Phillips, & Crombie, 2005;Gotteland et al, 2008).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations